2014
DOI: 10.1098/rsbl.2014.0533
|View full text |Cite
|
Sign up to set email alerts
|

Better the devil you know: avian predators find variation in prey toxicity aversive

Abstract: Toxic prey that signal their defences to predators using conspicuous warning signals are called ‘aposematic’. Predators learn about the toxic content of aposematic prey and reduce their attacks on them. However, through regulating their toxin intake, predators will include aposematic prey in their diets when the benefits of gaining the nutrients they contain outweigh the costs of ingesting the prey's toxins. Predators face a problem when managing their toxin intake: prey sharing the same warning signal often v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…This indicates that other factors, such as visual cues, might be more important than taste for influencing predators' initial decision to consume prey (Marples et al 1994;Ihalainen et al 2007), whereas prey toxicity and its physiological effects might drive later foraging behavior (Skelhorn et al 2016). Nevertheless, the ability to detect bitter taste might be important when predators are sampling prey with weaker chemical defenses or when defenses are more variable, which can increase the risk of ingesting toxins (Skelhorn and Rowe 2005;Barnett et al 2014). Furthermore, predators can gather social information about prey unpalatability by observing the disgust responses of other predators (Mason and Reidinger 1982;Johnston et al 1998;Skelhorn 2011;Thorogood et al 2018;Hämäläinen et al 2019a).…”
Section: Figurementioning
confidence: 99%
“…This indicates that other factors, such as visual cues, might be more important than taste for influencing predators' initial decision to consume prey (Marples et al 1994;Ihalainen et al 2007), whereas prey toxicity and its physiological effects might drive later foraging behavior (Skelhorn et al 2016). Nevertheless, the ability to detect bitter taste might be important when predators are sampling prey with weaker chemical defenses or when defenses are more variable, which can increase the risk of ingesting toxins (Skelhorn and Rowe 2005;Barnett et al 2014). Furthermore, predators can gather social information about prey unpalatability by observing the disgust responses of other predators (Mason and Reidinger 1982;Johnston et al 1998;Skelhorn 2011;Thorogood et al 2018;Hämäläinen et al 2019a).…”
Section: Figurementioning
confidence: 99%
“…If this was the case, it would lead to the intriguing possibility that large defended prey would benefit more from their defenses when they are less distinguishable from smaller and less energetically rewarding defended prey because of the uncertainty of the associated nutritional reward. This would be akin to the idea that birds find a toxic species more aversive if individuals vary in their toxicity, because the predator is less able to predict the toxin content of the prey and regulate its toxin intake (Barnett et al 2014; Speed and Ruxton 2014). Our results suggest that this idea could be extended to consider how the variability in nutrient content could also be a crucial factor in risky decision-making on toxic prey.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical studies following this approach have been important in demonstrating how warning signals are designed to enhance learned and unlearned avoidance in predators (e.g., Gittleman and Harvey 1980; Roper and Redston 1987; Rowe and Guilford 1996; Lindström et al 1999; Aronsson and Gambarale-Stille 2009; Svádová et al 2009), and how increasing the detectability, amount, or variability of toxicity can increase predator aversions (e.g., Skelhorn and Rowe 2006a, 2006b, 2006c; Barnett et al 2012, 2014). However, a recent study has shown that there is another intrinsic factor that affects foraging predators’ decisions to attack aposematic prey: the nutritional content of prey.…”
Section: Introductionmentioning
confidence: 99%
“…Variations in chemical defence within prey populations may, potentially, provide a considerable advantage for these populations in the face of a diverse complex of natural enemies (Speed et al 2012). In particular, some experimental studies have demonstrated that prey populations with polymorphic chemical defences sufer less from bird predation than do monomorphic populations (Skelhorn and Rowe 2005;Barnett et al 2014). Although the variation in chemical defence proiles may be genetically based (Eggenberger and Rowell-Rahier 1992;Holloway et al 1993), our current study showed that this variation in herbivorous insects at least partly depends on the host-plant species, even when the defensive chemicals are synthesised de novo.…”
Section: Mortality Due To Natural Enemiesmentioning
confidence: 99%